A multichannel ATM switch with output buffering. - Cheng, Tee-Hiang (Computer networks and ISDN systems.)
Multichannel transmission allows packets belonging to the same virtual circuit to be transmitted optimally over different channels interconnecting the same node-pair. Thus, it is able to give higher statistical multiplexing gain compared to conventional unichannel transmission, which requires all packets of a virtual circuit to use the same channel. An output-buffered space switch is proposed in this paper to facilitate multichannel transmission in Asynchronous Transfer Mode (ATM) networks. Unlike some other multichannel ATM switches, the proposed design does not give rise to out of sequence problems. Past studies have shown that conventional output-buffered space division switches have excellent throughput and delay performance. This paper shows that the effects of combining output-buffering and multichannel transmission give even better performance.